2011
DOI: 10.1029/2011gl048315
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fixation in the South Atlantic Gyre and the Benguela Upwelling System

Abstract: Dinitrogen (N2) fixation is recognized as an important input of new nitrogen (N) to the open ocean gyres, contributing to the export of organic matter from surface waters. However, very little N2‐fixation research has focused on the South Atlantic Gyre, where dust deposition of iron (Fe), an important micronutrient for diazotrophs, is seasonally low. Recent modeling efforts suggest that N2‐fixation may in fact be closely coupled to, and greatest in, areas of denitrification, as opposed to the oceanic gyres. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
105
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(118 citation statements)
references
References 32 publications
(37 reference statements)
11
105
2
Order By: Relevance
“…Our CARD-FISH observations expanded the geographic coverage of UCYN-A1 in symbiosis to the South Atlantic gyre and the southern Indian Ocean. In these regions, no records of the prymnesiophyte phylotypes or UCYN-A were documented previously, except occasional detections of UCYN-A nifH sequences (no clade distinction) in the Benguela upwelling system, in the Arabian Sea and near Madagascar (Mazard et al, 2004;Moisander et al, 2010;Sohm et al, 2011a). Moreover, our metabarcoding analysis represented the first detection of both hosts in the Red Sea and widened the presence of the UCYN-A2 host in the South Pacific, the Arabian Sea and the Mediterranean Sea, where only few nifH clones of UCYN-A2 were reported (Man-Aharonovich et al, 2007).…”
Section: Distribution Of a Prymnesiophyte-ucyn-a Symbiosis Am Cabellomentioning
confidence: 99%
“…Our CARD-FISH observations expanded the geographic coverage of UCYN-A1 in symbiosis to the South Atlantic gyre and the southern Indian Ocean. In these regions, no records of the prymnesiophyte phylotypes or UCYN-A were documented previously, except occasional detections of UCYN-A nifH sequences (no clade distinction) in the Benguela upwelling system, in the Arabian Sea and near Madagascar (Mazard et al, 2004;Moisander et al, 2010;Sohm et al, 2011a). Moreover, our metabarcoding analysis represented the first detection of both hosts in the Red Sea and widened the presence of the UCYN-A2 host in the South Pacific, the Arabian Sea and the Mediterranean Sea, where only few nifH clones of UCYN-A2 were reported (Man-Aharonovich et al, 2007).…”
Section: Distribution Of a Prymnesiophyte-ucyn-a Symbiosis Am Cabellomentioning
confidence: 99%
“…Recent studies demonstrate the presence and activity of diazotrophs in DIN-enriched environments such as the eastern tropical North Atlantic (Voss et al, 2004), the western English Channel (Rees et al, 2009), the Mekong River plume in the South China Sea (Grosse et al, 2010), the temperate NE American coast (Mulholland et al, 2012), and mesohaline temperate estuaries between the Baltic Sea and the North Sea (Bentzon-Tilia et al, 2015). Evidences of BNF have also been reported in upwelling systems such as the eastern equatorial Atlantic (Voss et al, 2004;Foster et al, 2009;Subramaniam et al, 2013), the Benguela upwelling system (Sohm et al, 2011;Benavides et al, 2014), and the region off central Chile (Raimbault and Garcia, 2008;.…”
Section: Introductionmentioning
confidence: 98%
“…marine microbiology | oligotrophic | evolution genomics | nitrogen fixation T he low availability of N (and fixed carbon) in the midlatitude upper oceans provides an important niche for autotrophic organisms that can fix atmospheric nitrogen, which can exert control over global primary production (1)(2)(3). Nitrogen fixation is a prokaryotic process with a high-energy demand, and oceanic cyanobacteria are known to be significant sources of this "new" nitrogen (nitrogen that is fixed from the atmosphere or NO 3 advected from depth) (4,5). Molecular field data have shown that a handful of cyanobacterial diazotrophs responsible for oligotrophic nitrogen fixation can reach relatively high cell numbers (6)(7)(8)(9)(10)(11)(12) and be of significant biogeochemical importance (13)(14)(15)(16).…”
mentioning
confidence: 99%